The life after death project - Davids, Paul; Johnson, Scot (Scientist); Sena-Shannon, Juanita; Yellow Hat Productions; Soundview Media Partners ([Reno, Nev.] : Yellow Hat Productions, 2013)
Noted film critic Pete Hammond calls this a great documentary and the world's first paranormal biography. After the death of science-fiction scholar Forrest J. Ackerman at age 92, several of his close friends (including the director of this film) were astonished to receive what seemed to be messages from him from "The Other Side." This thought-provoking film seriously considers whether Mr. Ackerman, an avowed atheist and skeptic with a mischievous sense of humor, fulfilled a promise he made to "drop a line" to friends after he died if he were to discover that life after death does exist. It's a true story filled with anomalies, extraordinary synchronicities and events that seem to defy scientific reason -- but the evidence for life after death presented in this film is new, startling and will prove convincing to many. Skeptic magazine publisher and author Michael Shermer contributes, too. However, we are reminded that skeptics once rejected scientific theories of germs, aviation and rocketry, all of which are commonplace today. With the participation of scientists at three American Universities,plus three apparently very gifted psychic mediums and some very famous authors (including Richard Matheson, Whitley Strieber and Dannion Brinkley), this film highlights recent computer research on "After Death Communication" by author/professor Dr. Gary Schwartz.
Originally released as a motion picture in 2013
Narrators: Scot Johnson, Juanita Sena-Shannon.
Apperaring as themselves: Richard Matheson, Whitley Strieber, Dannion Brinkley, Gary E. Schwartz, Michael Shermer, Forrest J. Ackerman, Mark Macy, Joe Moe, Sean Fernald.
Editor and cinematographer, Paul Davids ; music, Herman Beeftink, Errol G. Specter.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed January 29, 2018)
Keywords: Future life; Spiritualism; Immortality; Ackerman, Forrest J; Documentary films; Internet videos; Streaming video